An Exploratory Analysis of Patents in Fishing Technology - Sharma, Arpita; Ninan, Sunitha; P.S., Ananthan (Fishery Technology, 2025)
With growing importance of patents, its relevance and scope in fisheries sector, though not prominently felt so far, is an issue which needs to be addressed with urgency. Accordingly, a study was designed to document patents in fishing technology. First, data was examined with respect to trends in growth of patenting activity in India. Since year wise number of patents during period from 1913-2000 was very small, they were classified under four periods i.e., patenting activities before and after independence (1913-1947,1947-1970), before and after Indian Patent Act 1970 (1971- 1995) and before and after WTO era (1996-2000) so as to facilitate comparison. Patents maintained by Indian patent office and indexed under section 82 XIV (4): Fish and Fishing as per Indian classification key were grouped under the discipline 'fishing technology'. Total of 15 patents were granted during 1947-1970, 10 patents during 1971-2000 and 1 in post TRIPS period (1996-2000) suggesting a decline. From 1995-2002, 13 patent applications exist. Patents were under category fishhooks, fishing rods, fishing reels, baits, power block, short gun, tapes etc. used for fishing gear. Foreign applicants account for 78.38% of patents while 21.62% of patents are by Indians. Among domestic applicants, individuals account for 13.51% patents. Majority of applicants are foreign individuals accounting for 54.05% of patents granted.